TENDENCIES OF SOCIO-ECONOMIC DEVELOPMENT OF REGIONS OF UZBEKISTAN - Mullabayev Baxtiyarjon Bulturbayevich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article presents ideas and considerations about the organizational and economic foundations of the implementation of social and economic management of territories.